If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 7Sin(6x + 5) + 2Cos(3x + -2) Reorder the terms: Y = 7inS(5 + 6x) + 2Cos(3x + -2) Y = (5 * 7inS + 6x * 7inS) + 2Cos(3x + -2) Y = (35inS + 42inxS) + 2Cos(3x + -2) Reorder the terms: Y = 35inS + 42inxS + 2osC(-2 + 3x) Y = 35inS + 42inxS + (-2 * 2osC + 3x * 2osC) Y = 35inS + 42inxS + (-4osC + 6osxC) Solving Y = 35inS + 42inxS + -4osC + 6osxC Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 35inS + 42inxS + -4osC + 6osxC
| 5x-(-2x+1)=2 | | 2x+6+x+1=3(x-1)+6 | | 3x^2-8y^2=-5 | | 2/10➗3/100 | | 0=-18v^2+1476v-26600 | | 3(x-3)+4=2[-(x-5)-4(2x+1)] | | 4a^2+4a=-15 | | 4a^2+4=-15 | | 2x^1-1=0 | | 5x+60=5x | | 449/0.42= | | 16/5-20x=8 | | 2500+100x+x^2= | | log(5x+1)=1.2 | | y8/y3 | | 6+k^7=-2 | | 3x^3-5x-1=0 | | (36x^4+9)=0 | | 0.05(0.3x-0.06)= | | logx^729=3 | | 4n+5=2n+8 | | logx^36=2 | | 4y+49=27y+7 | | 4y+36=27y+7 | | 4.8x-4=4(1.2x-1) | | 4y+1636=27y+7 | | 8x-5x=x+8 | | 4y+25=27y+7 | | 4y+16=27y+7 | | y+2.4=7.33 | | 8+3n-5=9n+9-5 | | 2[2(3x-1)+3]-2(2x+5)=2(3x-3) |